PENGARUH PERMAINAN MENCARI HARTA KARUN TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 3 PEKANBARU - Andria, Iska; N, Zulkifli; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on field observations of the numeracy skills of students is still low and teachers are still teaching methods that dominate and not varied. So that learning needs to be given in the form of imaginative play. This study aims to determine the effect of a treasure hunt game against the numeracy skills of children aged 4-5 years in TK Negeri Pembina 3 Pekanbaru. The sample used in this study 13 children. The data collection techniques were used that observation. Data were analyzed using t-test using SPSS 17.0. The study hypothesis is that there is a significant influence on numeracy skills of children after applying the game in search of treasure. It can be seen from the analysis of data obtained t = 9.814 and p = 0.001. Because p <0.05 it can be concluded that there are differences in math ability protege significant after applying the dancing game treasure in learning. So it means Ho rejected and Ha accepted which means there is a very significant difference between before and after the experiment by applying the game in search of treasure. As for the influence of the game in search of treasure of the numeracy skills of children aged 4-5 years Tk In State Trustees 3 Pekanbaru is (P) = 63.16%.Keywords: Ability Numeracy, Looking for Treasure.